Stress change material and preparation method thereof
By introducing hydrophilic and hydrophobic chain segments into stress-changing materials and using water as plasticizers, the problem of existing thermotropic materials requiring high temperature activation is solved, and the dimensional changes and mechanical properties of the materials are maintained under water stimulation, which broadens its application scope.
Patent Information
- Application Number
- CN202411831923.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Existing thermogenic dimensional variation materials require higher temperature (>60°C) to activate segment movement, which limits its application, and the mechanical properties in water environments are degraded, making it difficult to meet actual needs.
By introducing hydrophilic and hydrophobic chain segments into stress-changing materials and adjusting their proportions and structures, water is used as a plasticizer to promote segment movement, achieving the effect of dimensional changes under water stimulation, while maintaining the mechanical properties of the material through the aggregation of the hydrophobic sections.
The volume expansion and shape recovery of the material under water stimulation are achieved, while maintaining excellent mechanical properties in the water environment, broadening the application range of the material.
Smart Images

Figure CN119823344A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane / polyurea, and more specifically, relates to a stress-changing material and a preparation method thereof. Background Art
[0002] Smart polymer materials that can change size under external signal stimulation (such as heat and light) have important applications in the fields of biomedicine and aerospace as vascular stents, surgical sutures and memory-type solar panels. For example, shape memory materials can be produced by using the melting temperature of crystalline polymers or adjusting the glass transition temperature of amorphous polymers. Introducing molecular units with high thermal expansion coefficients into polymer networks can produce thermally responsive volume expansion materials.
[0003] Common crystalline polymers include polyethylene, polypropylene, polyethylene oxide and polycaprolactone. Introducing thermotropic shape memory materials into crystalline polymers often faces problems such as high response temperature (>60°C) and poor mechanical properties, which limit their application. The preparation of polymer materials with high thermal expansion coefficients usually requires complex polymer design or the introduction of special chemical structural units (such as molecular cages), and the high cost limits their widespread application.
[0004] Whether it is volume expansion or shape memory materials, the microscopic essence of their size change is the movement of molecular chain segments. In view of the unique time-temperature equivalence characteristics of polymer materials, heating is usually used to activate the movement of chain segments, so that the material can produce controllable shape changes. In addition to thermal stimulation, mixing in plasticizers can promote the movement of chain segments to achieve reversible changes in the size of polymer materials, but thermogenic size-changing materials require higher temperatures (>60°C) to activate the movement of chain segments, which is not conducive to practical applications. In addition, the deformation mechanism of thermogenic size-changing materials is usually crystalline polymers, showing the mechanical properties of plastic materials, and the scope of application is limited. Water, as a natural green solvent, can be used as a plasticizer to adjust the movement of chain segments as needed. However, such polymer materials require complex structural designs, and the mechanical properties of the materials decrease significantly after absorbing water, and they do not yet have application prospects. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a stress-changing material (such as a polyurethane or polyurea material) that changes in size under water stimulation and a preparation method thereof. By adjusting the structure of the soft segment (i.e., the hydrophobic segment or the hydrophilic segment), the ratio of the hydrophilic segment to the hydrophobic segment, and the type of the chain extender, a stress-changing material that changes in size under water stimulation can be obtained, and the stress-changing material maintains excellent mechanical properties. The synthesis of the stress-changing material is divided into two steps. First, the soft segment raw material and the hard segment raw material (or diisocyanate) are mixed to obtain an isocyanate-terminated prepolymer, and then the chain extender is added to react to obtain the stress-changing material.
[0006] Specifically, in the present invention, hydrophilic segments are introduced into the stress-changing material, and water as a plasticizer can promote the movement of polyurethane or polyurea segments in the stress-changing material. By adjusting the structure of other components, the stress-changing material prepared by the present invention can expand in volume after absorbing water or achieve shape recovery with the assistance of a small amount of water. After absorbing water, the hydrophilic segments are rearranged, and the hydrophobic segments are aggregated together, and the mechanical strength of the material is maintained by hydrogen bond cross-linking.
[0007] To achieve the above objective, according to one aspect of the present invention, a stress-sensitive material is provided, characterized in that the stress-sensitive material comprises a hydrophobic segment and a hydrophilic segment.
[0008] Preferably, the raw material constituting the hydrophobic segment is selected from hydrophobic polymer polyols, preferably at least one selected from polytetramethylene glycol, polycarbonate glycol, polydimethylsiloxane glycol and polycaprolactone glycol.
[0009] Preferably, the raw material constituting the hydrophilic segment is selected from hydrophilic polymer polyols, preferably selected from one or both of polyethylene glycol and polypropylene glycol.
[0010] Preferably, the stress-changing material further comprises a hard segment, and the raw material for preparing the hard segment is selected from diisocyanate. As a further preferred embodiment of the present invention, the diisocyanate is selected from aliphatic diisocyanate and aromatic diisocyanate, preferably selected from one or more of isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate and diphenylmethane diisocyanate.
[0011] Preferably, the stress-changing material further comprises a chain segment derived from a chain extender, wherein the chain extender is selected from at least one of cyclohexanediamine (eg, 1,4-cyclohexanediamine), N,N-dihydroxyethyloxamide, hexanediamine and N,N-bis(3-aminopropyl)methylamine.
[0012] Preferably, the molar ratio of the hydrophilic polymer polyol to the hydrophobic polymer polyol is (0.5-4):1;
[0013] The molar ratio of the diisocyanate to the total amount of the polymer polyol (i.e., hydrophilic polymer polyol + hydrophobic polymer polyol) is (1.4-2.6):1;
[0014] The molar ratio of the amount of the chain extender to the total amount of the polymer polyol (i.e., the hydrophilic polymer polyol + the hydrophobic polymer polyol) is (0.4-1.6):1;
[0015] As a further preferred embodiment of the present invention, the number average molecular weight of the hydrophilic polymer polyol and the hydrophobic polymer polyol are both 600 to 4000, for example, 600, 800, 1000, 2000, 3000 or 4000;
[0016] According to another aspect of the present invention, the present invention provides a method for preparing the above-mentioned stress-changing material, characterized in that it comprises the following steps:
[0017] (1) using a hydrophilic polymer polyol and a hydrophobic polymer polyol as soft segment raw materials and a diisocyanate as a hard segment raw material, subjecting the soft segment raw materials and the hard segment raw materials to a polycondensation reaction in the presence of a catalyst to obtain an isocyanate-terminated prepolymer;
[0018] (2) The isocyanate-terminated prepolymer obtained in step (1) is mixed with a chain extender, and a chain extension reaction is carried out under the action of a catalyst to obtain the stress-changing material.
[0019] Preferably, in step (1), the reaction temperature of the polycondensation reaction is 30 to 70° C., and the reaction time is 6 to 24 hours.
[0020] Preferably, in step (2), the reaction temperature of the chain extension reaction is 30-70° C., and the reaction time is 6-24 h.
[0021] Preferably, step (1) or step (2) is performed under an inert atmosphere.
[0022] Preferably, the reaction of step (1) is carried out in the presence of a solvent, preferably, the solvent is at least one of tetrahydrofuran, N,N'-dimethylformamide or N,N'-dimethylacetamide; preferably, step (1) is carried out under anhydrous conditions, for example, the solvent is an anhydrous solvent, for example, at least one of anhydrous tetrahydrofuran, anhydrous N,N'-dimethylformamide or anhydrous N,N'-dimethylacetamide.
[0023] Preferably, in step (1) or step (2), the catalyst is selected from amine, tin or bismuth catalysts, for example, the catalyst is selected from at least one of dibutyltin dilaurate, dimethylcyclohexylamine and bismuth isooctanoate. The content of the catalyst is not particularly limited, as long as the polycondensation reaction or chain extension reaction can occur.
[0024] Beneficial effects of the present invention:
[0025] 1. The water-stimulated dimensional change stress-changing material provided by the present invention comprises both a hydrophilic polymer polyol and a hydrophobic polymer polyol. According to the composition of the materials, it can undergo two shape changes in a water environment, namely, swelling due to water absorption and shape recovery due to water acting as a plasticizer to activate the movement of polymer chain segments;
[0026] 2. In the stress-sensitive material of the present invention, the polarity difference between the hard segment urethane / urea group and the soft segment polymer polyol promotes the formation of a microphase separation structure. The hard segment aggregates as the dispersed phase and their hydrogen bond interactions give the polyurethane / polyurea excellent mechanical properties. In particular, when the material absorbs water, the hydrophobic segments (including urethane / urea groups) gather together and serve as physical crosslinking points to maintain the mechanical stability of the material.
[0027] 3. The stress-sensitive material provided by the present invention can be prepared on a large scale and has a linear structure and can be processed by solution or heat.
[0028] In summary, the stress-responsive material prepared by the present invention can undergo dimensional changes in two ways under water stimulation: first, it absorbs a large amount of water to induce rearrangement of hydrophilic chain segments and achieve volume expansion; second, it absorbs a small amount of water as a plasticizer to promote chain segment movement and achieve shape recovery; at the same time, thanks to the introduction of hydrophobic segments, polyurethane / polyurea can still maintain sufficient mechanical strength even in a water environment, broadening the application range of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the structure of the polyurethane prepared in Example 1.
[0030] Figure 2 This is the infrared spectrum of the polyurethane prepared in Example 1.
[0031] Figure 3 Schematic diagram of the stress-strain curve of the polyurethane prepared in Example 1 before and after water absorption.
[0032] Figure 4 This is a diagram showing the diameter change of the polyurethane prepared in Example 1 before and after absorbing water.
[0033] Figure 5 This is a diagram showing the shape memory effect of the polyurethane prepared in Example 2 after being stimulated by water.
[0034] Figure 6 Schematic diagram of the stress-strain curve of the polyurethane prepared in Example 3 before and after water absorption.
[0035] Figure 7 This is a diagram showing the diameter change of the polyurethane prepared in Example 3 before and after absorbing water.
[0036] Figure 8 This is a diagram showing the diameter change of the polyurethane prepared in Example 4 before and after it is stimulated by water to induce shape memory.
[0037] Fig. 9 Schematic diagram of the force-strain curve of the polyurethane pipe prepared in Example 5 before and after water absorption.
[0038] Fig.10Schematic diagram of the stress-strain curve of the polyurethane prepared in Comparative Example 1 before and after water absorption.
[0039] Fig.11 This is a picture of the actual shape of the polyurethane prepared in Comparative Example 2 after absorbing water and drying.
[0040] Fig.12 Schematic diagram of the dimensional change of stress-sensitive materials under water stimulation. DETAILED DESCRIPTION
[0041] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0042] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0043] Example 1
[0044] The polyurethane prepared in this embodiment has a basic structure as shown in Figure 1 As shown. Polyethylene glycol (4mmol) with a number average molecular weight of 1000 and polytetrahydrofuran (1mmol) with a number average molecular weight of 4000 were added to a round-bottom flask, and vacuum was continuously applied at 100°C for 2h to remove trace amounts of water. Then the temperature was lowered to 60°C, anhydrous tetrahydrofuran was added, and the mixture was stirred and dissolved to obtain a transparent and uniform reaction solution. Dicyclohexylmethane diisocyanate (7mmol) and 3 drops of dibutyltin dilaurate were added to the reaction solution, and N,N-dihydroxyethyl oxamide (2mmol) was added after reacting for 8h under an inert atmosphere, and the reaction was continued for 12h. The reaction solution was poured into a polytetrafluoroethylene mold, dried at room temperature for 24h, and then transferred to a vacuum oven and dried at 60°C for 24h to obtain a polyurethane film material.
[0045] Fourier transform infrared spectroscopy was used to characterize the chemical structure of polyurethane. The test results are as follows: Figure 2 As shown, wave number 3529-3316cm -1 It is the NH stretching vibration peak in carbamate; the wave number range is 2935~2864cm -1 -CH3 and -CH2- stretching vibration peaks. Wave number 1703cm -1 and 1677cm -1 The peaks are the stretching vibration peaks of C=O in carbamate and oxalamide respectively. The infrared results show that the polyurethane is successfully prepared.
[0046] The mechanical properties of polyurethane are tested as follows: the polyurethane film material is cut into standard shapes and tested using a universal testing machine. Figure 3 As shown, the breaking strength of the polyurethane prepared in this example before absorbing water is 2.4 MPa, and the breaking elongation is 1600%.
[0047] In order to further characterize the mechanical properties of polyurethane after water absorption, the prepared polyurethane was placed in room temperature water for 1 hour. Figure 3 The results show that after absorbing water, the breaking strength of polyurethane increases to 9.0 MPa, and the breaking elongation decreases to 1200%. This is because after absorbing water, it forms a microphase separation structure, and the hydrophobic segments (including urethane) gather together as physical crosslinking points to enhance the modulus of the material.
[0048] Further verification of the dimensional change of polyurethane after water stimulation. The tubular polyurethane material was immersed in saline for 2.5 minutes. The weight of the polyurethane increased from 0.0576g to 0.0836g, and the water absorption rate was 45%. Figure 4 As shown, the diameter of the polyurethane tube expands from 7.30 mm to 9.74 mm, and the dimensional change rate (according to the diameter) is 35%.
[0049] Example 2
[0050] Add polypropylene glycol (1mmol) with a number average molecular weight of 600 and polycarbonate (2mmol) with a number average molecular weight of 1000 to a round-bottom flask, and continue to evacuate at 100℃ for 2h to remove traces of water. Then cool to 60℃, add anhydrous tetrahydrofuran, and stir to dissolve to obtain a transparent and uniform reaction solution. Add diphenylmethane diisocyanate (7.8mmol) and 5 drops of dimethylcyclohexylamine to the reaction solution and react for 12h under an inert atmosphere. Then cool to 30℃ and add 1,4-cyclohexanediamine (4.8mmol), continue to react for 12h, pour the reaction solution into a polytetrafluoroethylene mold, dry at room temperature for 24h, transfer to a vacuum oven, and dry at 60℃ for 24h to obtain a polyurethane film material.
[0051] Verify the shape memory function of polyurethane after being stimulated by water. The shape memory function exhibited by the polymer originates from the stimulus responsiveness of the molecular chain. After heating, the mobility of the polymer chain segments is activated, and the temporary shape can be edited. After cooling, the movement of the chain segments is frozen, and the material acquires a temporary shape. After being stimulated by external factors, the movement of the chain segments is activated again, and the material returns to its original shape under the action of the stationary phase. Heat the polyurethane film material to 60°C and apply a temporary shape, maintain the shape and cool down to 10°C to fix the temporary shape. Soak the polyurethane film with a fixed temporary shape in water (25±5°C) and observe the degree of shape recovery. Figure 5 As shown, the stress-changing material of the present invention can recover to its original shape within 2 minutes. Water as a plasticizer can activate the movement of the chain segments, and the rigid polycarbonate and urethane groups act as stationary phases to drive the material to recover to its original shape.
[0052] Example 3
[0053] Add branched polyethylene glycol (1mmol) with a number average molecular weight of 1000 and polycaprolactone (1mmol) with a number average molecular weight of 2000 to a round-bottom flask, and continue to vacuum at 100℃ for 2h to remove traces of water. Cool down to 70℃, add anhydrous N,N'-dimethylformamide, stir and dissolve to obtain a transparent and uniform reaction solution. Add isophorone diisocyanate (4mmol) and 4 drops of bismuth isooctanoate to the reaction solution and react for 6h under an inert atmosphere. Then cool to 30℃ and add hexamethylenediamine (2mmol), continue to react for 12h, pour the reaction solution into a polytetrafluoroethylene mold, dry at 80℃ for 24h, transfer to a vacuum oven, and dry at 60℃ for 24h to obtain a polyurethane membrane material.
[0054] The mechanical properties of polyurethane were tested using the same test method as in Example 1. The test results are as follows: Figure 6 As shown in the figure, the breaking strength of the polyurethane prepared in this embodiment before water absorption is 6.8 MPa, and the breaking elongation is 410%. After water absorption, the breaking strength of the polyurethane increases to 9.2 MPa, and the breaking elongation decreases to 310%. This is because water absorption promotes the formation of a microphase separation structure, and the hydrophobic segments (including urethane / urea groups) gather together as physical crosslinking points to enhance the modulus of the material.
[0055] To further verify the dimensional changes of polyurethane after being stimulated by water, the tubular polyurethane material was immersed in saline for 3 minutes. Figure 7 As shown, the diameter of the polyurethane tube expands from 7.73 mm to 8.73 mm, and the dimensional change rate (according to the diameter) is 13%.
[0056] Example 4
[0057] Add polyethylene glycol (2 mmol) with a number average molecular weight of 2000 and polydimethylsiloxane (1 mmol) with a number average molecular weight of 3000 to a round-bottom flask, and continue to vacuum at 100°C for 2 hours to remove traces of water. Cool down to 70°C, add anhydrous N,N'-dimethylacetamide, and stir to dissolve to obtain a transparent and uniform reaction solution. Add hexamethylene diisocyanate (6.6 mmol) and 3 drops of bismuth isooctanoate to the reaction solution and react for 6 hours under an inert atmosphere. Then cool to 30°C and add N,N-bis(3-aminopropyl)methylamine (3.6 mmol), continue to react for 12 hours, pour the reaction solution into a polytetrafluoroethylene mold, dry at 80°C for 24 hours, transfer to a vacuum oven, and dry at 60°C for 24 hours to obtain a polyurethane membrane material.
[0058] Heat the polyurethane tube to 60℃ and apply pressure to flatten it, then cool it down to 10℃ to fix the temporary shape. Soak the temporarily shaped tube in water (25±5℃) and observe the degree of shape recovery. Figure 8 As shown in Figure 2, the tube can recover within 2 minutes, and the diameter of the tube increases by 19% compared to the original shape. Water as a plasticizer can activate the chain segment motion, and the rigid polycarbonate and urethane groups act as stationary phases, driving the recovery of the tube and further increasing the diameter of the tube.
[0059] Example 5
[0060] After removing water, polypropylene glycol (0.5 mol) with a number average molecular weight of 2000 and polycarbonate (0.25 mol) with a number average molecular weight of 2000 were dissolved in anhydrous N, N'-dimethylformamide, dicyclohexylmethane diisocyanate (1.5 mol) and 12 ml of dimethylcyclohexylamine were added to the reaction solution, the temperature was raised to 70°C, and the reaction was carried out for 8 hours under an inert atmosphere. Then the temperature was lowered to 30°C and 1,4-cyclohexanediamine (0.75 mol) was added, and the reaction was continued for 12 hours. The reaction solution was poured into a polytetrafluoroethylene mold, dried at room temperature for 24 hours, and then transferred to a vacuum oven and dried at 60°C for 24 hours to obtain a polyurethane film material.
[0061] The universal testing machine is used to test the breaking force of the polyurethane pipe before and after absorbing water. Fig. 9 This is the tensile curve of the polyurethane pipe. The breaking force of the pipe body before absorbing water is 16N, and it increases to 19N after absorbing water. Water can cause it to form a microphase separation structure and further improve the strength of the material.
[0062] Comparative Example 1
[0063] Add polytetrahydrofuran (2 mmol) with a number average molecular weight of 4000 to a round-bottom flask, and continue to evacuate at 100°C for 2 hours to remove traces of water. Then cool to 60°C, add anhydrous tetrahydrofuran, and stir to dissolve to obtain a transparent and uniform reaction solution. Add dicyclohexylmethane diisocyanate (4 mmol) and 3 drops of dibutyltin dilaurate to the reaction solution, react for 8 hours under an inert atmosphere, then add N,N-dihydroxyethyl oxamide (2 mmol), continue to react for 12 hours, pour the reaction solution into a polytetrafluoroethylene mold, dry at room temperature for 24 hours, and then transfer to a vacuum oven and dry at 60°C for 24 hours to obtain a polyurethane film material.
[0064] The mechanical properties of polyurethane were tested using the same test method as in Example 1. The test results are as follows: Fig.10As shown, the breaking strength of the polyurethane prepared in this comparative example before water absorption is 3.5 MPa, and the breaking elongation is 525%. After water absorption, the breaking strength of the polyurethane drops to 1.9 MPa, and the breaking elongation drops to 170%. This is because the lack of hydrophilic soft segments makes the microphase separation structure after water absorption not obvious, and the water molecules reduce the free space between the molecular chains and destroy some hydrogen bonds, resulting in a decrease in modulus and toughness.
[0065] Comparative Example 2
[0066] Add polyethylene glycol (2mmol) with a number average molecular weight of 1000 to a round-bottom flask, and continue to evacuate at 100℃ for 2h to remove traces of water. Then cool to 60℃, add anhydrous tetrahydrofuran, and stir to dissolve to obtain a transparent and uniform reaction solution. Add dicyclohexylmethane diisocyanate (3mmol) and 3 drops of dibutyltin dilaurate to the reaction solution, react for 8h under an inert atmosphere, then add N,N-dihydroxyethyl oxamide (1mmol) and continue to react for 12h. Pour the reaction solution into a polytetrafluoroethylene mold, dry at room temperature for 24h, then transfer to a vacuum oven and dry at 60℃ for 24h to obtain a polyurethane film material.
[0067] The material has poor mechanical properties and cannot maintain its shape after absorbing water and drying. Fig.11 As shown, this is because the large amount of hydrophilic soft segments leads to a lower modulus of the material before water absorption.
[0068] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A stress-sensitive material, characterized in that: The stress-change material comprises a hydrophobic segment and a hydrophilic segment.
2. The stress-changing material according to claim 1, characterized in that: The raw material constituting the hydrophobic segment is selected from hydrophobic polymer polyols, preferably at least one selected from polytetramethylene glycol, polycarbonate glycol, polydimethylsiloxane glycol and polycaprolactone glycol. Preferably, the raw material constituting the hydrophilic segment is selected from hydrophilic polymer polyols, preferably selected from one or both of polyethylene glycol and polypropylene glycol.
3. The stress-changing material according to claim 1, characterized in that: The stress-changing material further comprises a hard segment, and the raw materials for preparing the hard segment are selected from diisocyanate. Preferably, the diisocyanate is selected from aliphatic diisocyanates and aromatic diisocyanates, preferably one or more selected from isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate and diphenylmethane diisocyanate. Preferably, the stress-changing material further comprises a chain segment derived from a chain extender, wherein the chain extender is selected from at least one of cyclohexanediamine, N,N-dihydroxyethyloxamide, hexamethylenediamine and N,N-bis(3-aminopropyl)methylamine.
4. The stress-changing material according to claim 1, characterized in that: The number average molecular weights of the hydrophilic polymer polyol and the hydrophobic polymer polyol are both 600-4000.
5. The stress-changing material according to claim 1 or 2, characterized in that: The molar ratio of the hydrophilic polymer polyol to the hydrophobic polymer polyol is (0.5-4):1; Preferably, the molar ratio of the diisocyanate to the total amount of the polymer polyol is (1.4-2.6):1; The molar ratio of the amount of the chain extender to the total amount of the polymer polyol is (0.4-1.6):
1.
6. The method for preparing the stress-sensitive material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) using a hydrophilic polymer polyol and a hydrophobic polymer polyol as soft segment raw materials and a diisocyanate as a hard segment raw material, subjecting the soft segment raw materials and the hard segment raw materials to a polycondensation reaction in the presence of a catalyst to obtain an isocyanate-terminated prepolymer; (2) The isocyanate-terminated prepolymer obtained in step (1) is mixed with a chain extender, and a chain extension reaction is carried out under the action of a catalyst to obtain the stress-changing material.
7. The preparation method according to claim 6, characterized in that: In step (1), the reaction temperature of the polycondensation reaction is 30 to 70° C., and the reaction time is 6 to 24 hours. Preferably, in step (2), the reaction temperature of the chain extension reaction is 30-70° C., and the reaction time is 6-24 h.
8. The preparation method according to claim 6, characterized in that: Step (1) or step (2) is carried out under an inert atmosphere.
9. The preparation method according to claim 6, characterized in that: The reaction in step (1) is carried out in the presence of a solvent. Preferably, the solvent is at least one of tetrahydrofuran, N,N'-dimethylformamide or N,N'-dimethylacetamide.
10. The preparation method according to claim 6, characterized in that: In step (1) or step (2), the catalyst is selected from amine, tin or bismuth catalysts.
Citation Information
Patent Citations
Method for preparing shape memory polyurethane resin
CN101921382A
Ultra-high-strength polyurethaneurea supermolecular hydrogel and preparation method thereof
CN103992458A
Water response shape memory polyurethane and preparation method therefor
CN105237714A
Polyurethane, preparation method and applications thereof
CN110358044A
High-strength room-temperature self-repairing polyurethane elastomer based on multiple dynamic reversible effects as well as preparation and application of high-strength room-temperature self-repairing polyurethane elastomer
CN110790888A